An Examination from the Perspective of Islamic Law in the Context of the Health Condition Required in Judges - Gülengül, Esra (Fırat University, 2022)
Throughout history, judges have been involved in delivering rights to the owner and ensuring justice. Due to this mission of theirs, special attention has been attributed to the qualifications that the people who serve as judges should have. Likewise, it is noteworthy that in the fiqh (Islamic law) books, which deal with qa?a? (judiciary) and q??? (judge) in a separate chapter, there is also an emphasis on health among the qualities that judges should have. Accordingly, the judge must first have full capacity for action in terms of mental health. Depending on mental health, there is a consensus among fuqaha that the mentally disabled, as well as the interdicted persons such as the libertines, cannot be judges because they do not have the decision-making capacity. Secondly, in order to make a legally valid judgment, the judge must be in the perfect creation condition (kâmilu’l-?ilkat) in terms of sight, hearing, and speech. Preferably, although the expectation was in this direction, it was accepted that people who had loss of sight, hearing, and speech to an extent that would not prevent them from making judgements could serve as judges. In determining these criteria, witnessing was placed in the centre as a criterion. The fact that the provisions related to the health condition sought in judges in the book and sunnah were not explicitly mentioned paved the way for the discussion of the subject within the framework of mental deductions rather than as nass (words of God and the prophet). Our study aims to examine the health condition required in judges in the context of fiqh discussions and to determine the evidence taken as a basis for basing the various opinions mentioned in the sources. While examining the opinions of the fuqaha on the determined subject, phenomenological analysis and historical research methods were used among the qualitative research models. However, tahric, a traditional method in fiqh, was also applied when necessary.

Tarih boyunca hâkimler, hakların sahibine teslim edilmesi ve adaletin sağlanmasında görev almışlardır. Onların bu misyonu sebebiyle, hâkimlik yapacak kişilerin sahip olması gereken niteliklere özel olarak önem verilmiştir. Aynı şekilde kazâ ve kâdîyı ayrı bir bölümde ele alan fıkıh kitaplarında da hâkimlerin sahip olması gereken nitelikler içerisinde sağlığa ayrıca vurgu yapılması dikkat çekmektedir. Buna göre hâkimin öncelikle akıl sağlığı açısından tam fiil ehliyetine sahip olması gerekir. Akıl sağlığına bağlı olarak zihinsel engellilerin yanı sıra sefih gibi kısıtlıların kazâ velayetine sahip olmadıkları için hâkimlik yapamayacakları konusunda fakihlerin ittifakı vardır. İkinci olarak hâkimin hukuken geçerli bir yargılama yapabilmek için görme, işitme ve konuşma yönünden de kâmilü’l-hilkat yani mükemmel yaratılışta olması gerekir. Tercihen beklenti bu yönde olmakla birlikte, yargılamaya mâni olmayacak derecede görme, işitme ve konuşma kaybı olan kişilerin hâkimlik yapabilecekleri kabul edilmiştir. Bu kriterlerin belirlenmesinde kıstas olarak özellikle şahitlik merkeze alınmıştır. Kitab ve sünnette hâkimlerde aranan sağlık şartıyla ilgili hükümlerin açıkça zikredilmeyişi, konunun nasslardan ziyade akli istidlaller çerçevesinde tartışılmasına zemin hazırlamıştır. Çalışmamız, hâkimlerde aranan sağlık şartını fıkhî tartışmalar bağlamında incelemeyi ve kaynaklarda zikredilen muhtelif görüşlerin temellendirilmesinde esas alınan delilleri belirlemeyi gaye edinmektedir. Belirlenen konuyla ilgili fakihlerin görüşleri incelenirken nitel araştırma modelleri arasından daha çok fenomenolojik çözümleme ile tarihsel araştırma yöntemleri uygulanmıştır. Bununla birlikte yeri geldikçe fıkıhta geleneksel bir metot olan tahrice de müracaat edilmiştir.
İslam Hukuku Perspektifinden Hâkimlerde Aranan Sağlık Şartı Özelinde Bir İnceleme
Keywords: Religious Studies; Din Araştırmaları